فاعلية الاتصال الداخلي في مواجهة الضغط المهني - قدوري, الحاج (جامعة الوادي University of Eloued, 2016)
تهدف الدراسة الحالية إلى الكشف عن فاعلية الاتصال الداخلي في مواجهة الضغط المهني من وجهة نظر الممرضين العاملين في مستشفى محمد بوضياف بورقلة, وتبحث في متغيرات محددة وهي الاختلاف بين أفراد العينة على مستوى الجنس(ذكور وإناث) والسن والأقدمية, ومن أجل تحقيق أهداف الدراسة واختبار الفرضيات قمنا بإتباع الخطوات والمبادئ والقواعد الأساسية للمنهج الوصفي الذي يتناسب ودراستنا معتمدين على استبيان لغرض جمع البيانات بعد التأكد من خصائصه السيكومترية وبعد معالجة البيانات باستخدام مجموعة من الأساليب الإحصائية المناسبة, توصلنا إلى أن الاتصال الداخلي فعال في مواجهة الضغط المهني من وجهة نظر الممرضين, مع عدم وجود فروق بين أفراد العينة في ذالك باختلاف الأقدمية والسن والجنس(ذكور وإناث). The present study aims to reveal the effectiveness of internal communication in confrontation with occupational stress from the perspective of nurses working at Mohamed Boudiaf Hospital in Ouargla. The study seeks to identify specific variables which are the differences between members of the sample according to the level of sex(males, females), age and seniority. In order to achieve the objectives of the study and testing of hypotheses, we followed the steps and the basic principles and rules of the descriptive approach which appropriates our study. We used a questionnaire for the purpose of collecting data after the confirmation of its psychometric properties. After processing the data using a set of appropriate statistical methods, we found that internal communication is effective in facing occupational stress from the perspective of nurses, with no differences between the sample members according to seniority, age and sex(males, females)
من وجهة نظر الممرضين العاملين في مستشفى محمد بوضياف بورقلة
مقال
Keywords: الاتصال الداخلي, الضغط المهني; internal communication, occupational stress